A facile method for the synthesis of a porous cobalt oxide–carbon hybrid as a highly efficient water oxidation catalyst. Issue 5 (14th January 2016) - Zhang, Mei; Huang, Yong-Liang; Wang, Jia-Wei; Lu, Tong-Bu
Abstract : A cobalt oxide–carbon hybrid was synthesized, which exhibited outstanding chemical, photochemical and electrochemical water oxidation catalytic activity. Abstract : A main challenge for light-driven water splitting is the development of efficient and economical water oxidation catalysts (WOCs). Herein, we developed a facile approach for the preparation of a porous cobalt oxide–carbon hybrid, which was prepared by carbonizing in an inert atmosphere and subsequently air-calcining nanocrystals of zeolite imidazole framework-67 (ZIF-67), and utilized as an efficient WOC. Using Ru(bpy)3 (PF6 )3 as an oxidant, we got a record catalytic turnover number (TON) and a turnover frequency (TOF) of 910 ± 21 and 14.6 ± 0.4 s −1 per cobalt atom, respectively. In addition, the synthesized catalyst can also act as an efficient electrochemical WOC, with a low OER overpotential of 0.36 V at 10.0 mA cm −2 in a pH 13 medium. The superior catalyst performance can be attributed to the homogeneous dispersion of CoO x and in situ formed porous carbon, and the presence of nitrogen in the catalyst may also be attributed to its high catalytic activity.